Is total system cost minimization fair to all the actors of an energy system? Not according to game theory. (15th January 2022) - Fischer, Robert; Toffolo, Andrea
Abstract: A common approach to energy system optimization is to minimize overall costs at system level, regardless of the actors actually bearing those costs. This paper presents an approach inspired by Nash game theory concepts, in which the actors involved in an energy system determine their optimal strategies according to their own economic interests (profit functions) in a non-cooperative or in a cooperative way. A simple case study, considering an electric utility and individual heating consumers in the municipal energy system of a small town in northern Sweden, shows the differences between the two approaches. The game theory approach is able to represent more realistic interactions among the actors of an energy system, fair in fulfilling their conflicting economic interests, and, therefore, a more suitable tool for decision makers evaluating the impacts of policy instruments. Highlights: The transition to decarbonized energy systems will make costs increase. Total system cost minimization overlooks the allocation of these increased costs. A game theory approach considers the profit functions of system actors. The economic interests of the actors are preserved and harmonized fairly. The point of view of the actors is more suitable to evaluate policy instruments.